Colon and rectal surgery : anorectal operations - Wexner, Steven D.; Fleshman, James (Philadelphia : Wolters Kluwer/Lippincott Williams & Wilkins Health, 2012)
"Master Techniques in General Surgery: Colon and Rectal Surgery: Anorectal Operations is a volume in a series that presents common and advanced procedures in the major subspecialities of general surgery. The series is overseen by Josef F. Fischer, MD, editor of the classic two-volume reference Mastery of Surgery. Master Techniques in General Surgery: Colon and Rectal Surgery: Anorectal Operations is written by acknowledged master surgeons, emphasizes surgical procedures, and is lavishly illustrated with original full-color drawings. The contributors fully explain their preferred techniques in step-by-step, thoroughly illustrated detail, assess indications and contraindications, offer guidelines on preoperative planning, and discuss outcomes, complications, and follow-up. Coverage includes hemorrhoidectomies, anal fistula and sphincter procedures, procedures for perineal prolapse and excision of rectal carcinoma, among others. A companion website will offer fully searchable content of the book, an image bank, and procedural videos"--Provided by publisher.
part I. Hemorrhoidectomy -- part II. Anal fistula -- part III. Rectovaginal fistula -- part IV. Operations for fecal incontinence -- part V. Perineal prolapse repair -- part VI. Sphincterotomy--lateral -- part VII. Presacral tumors -- part VIII. Local excision of rectal carcinoma -- part IX. Rectocele -- part X. Muscle flaps -- part XI. Anal and pilonidal flaps.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Colon (Anatomy) -- Surgery; Rectum -- Surgery; Electronic books